Lithium limits trimethyltin‐induced cytotoxicity and proinflammatory response in microglia without affecting the concurrent autophagy impairment. Issue 2 (25th May 2016) - Fabrizi, Cinzia; Pompili, Elena; Somma, Francesca; De Vito, Stefania; Ciraci, Viviana; Artico, Marco; Lenzi, Paola; Fornai, Francesco; Fumagalli, Lorenzo
Abstract: Trimethyltin (TMT) is a highly toxic molecule present as an environmental contaminant causing neurodegeneration particularly of the limbic system both in humans and in rodents. We recently described the occurrence of impairment in the late stages of autophagy in TMT‐intoxicated astrocytes. Here we show that similarly to astrocytes also in microglia, TMT induces the precocious block of autophagy indicated by the accumulation of the autophagosome marker, microtubule associated protein light chain 3. Consistent with autophagy impairment we observe in TMT‐treated microglia the accumulation of p62/SQSTM1, a protein specifically degraded through this pathway. Lithium has been proved effective in limiting neurodegenerations and, in particular, in ameliorating symptoms of TMT intoxication in rodents. In our in vitro model, lithium displays a pro‐survival and anti‐inflammatory action reducing both cell death and the proinflammatory response of TMT‐treated microglia. In particular, lithium exerts these activities without reducing TMT‐induced accumulation of light chain 3 protein. In fact, the autophagic block imposed by TMT is unaffected by lithium administration. These results are of interest as defects in the execution of autophagy are frequently observed in neurodegenerative diseases and lithium is considered a promising therapeutic agent for these pathologies. Thus, it is relevant that this cation can still maintain its pro‐survival and anti‐inflammatory role in conditions of autophagy block. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Trimethyltin (TMT) is a highly toxic molecule present as an environmental contaminant causing neurodegeneration particularly of the limbic systemboth in humans and in rodents. We recently described the occurrence of impairment in the late stages of autophagy in TMT‐intoxicated astrocytes. Here we show that similarly to astrocytes also in microglia, TMT induces the precocious block of autophagy indicated by the accumulation of the autophagosome marker, microtubule associated protein light chain 3.